AN ANALYSIS OF COMMUNICATION STRATEGIES IN EFL TEACHING AND LEARNING AT XI IPA 1 IN SMA NEGERI 1 KUTA UTARA - ., Ni Wayan Novita Yuliantari; ., Prof. Dr.I Ketut Seken,MA; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian deskriptif kualitatif ini bertujuan untuk menemukan (1) tipe dari communication strategies yang digunakan oleh guru dan siswa selama proses belajar mengajar Bahasa Inggris, (2) tipe communication strategies yang paling banyak digunakan oleh guru dan siswa, (3) alasan dalam menggunakan communication strategies di proses belajar dan mengajar. Subyek penelitian ini adalah guru Bahasa Inggris dan siswa dari kelas XI IPA 1 di SMA Negeri 1 Kuta Utara. Sementara itu, obyek penelitian adalah communication strategies yang digunakan oleh guru dan siswa selama proses belajar dan mengajar Bahasa Inggris. Hasil dari penelitian ini menunjukkan bahwa guru menggunakan sembilan tipe dari communication strategies berdasarkan Dornyei’s theory sebagai berikut message abandonment, circumlocution, approximation, use of all-purpose words, prefabricated patterns, non-linguistic signals, literal translation, code switching, dan time-gaining strategy. Sementara itu, ada sebelas tipe dari communication strategies yang digunakan oleh siswa, antara lain message abandonment, topic avoidance, circumlocution , approximation, word coinage, prefabricated patterns, non-linguistic signals, literal translation, code switching, appeal for help, dan time-gaining strategy. Communication strategy yang paling banyak digunakan oleh guru dan siswa adalah code switching dan time-gaining strategy. Ada dua alasan utama guru dalam penggunaan communication strategies yaitu untuk membantu siswa memahami pelajaran dan menghindari kesalahpahaman dalam penguasaan materi. Sementara itu siswa menggunakan communication strategies dikarenakan oleh kesulitan bahasa dan ketakutan untuk membuat kesalahan. Kata Kunci : communication strategies, Dornyei’s theory, EFL This descriptive qualitative study aimed at finding out (1) the types of communication strategies which were used by the teacher and the students during English as Foreign Language (EFL) teaching and learning, (2) the types of communication strategies used most frequently by the teacher and the students, (3) the reasons of using the communication strategies in EFL teaching and learning process. The subjects were the English teacher and the students of XI IPA 1 of SMA Negeri 1 Kuta Utara. Meanwhile, the object of this study was communication strategies used by the teacher and the students during EFL teaching and learning. The results of this study showed that the teacher applied nine types of communication strategies based on Dornyei’s theory, namely, message abandonment, circumlocution, approximation, use of all-purpose words, prefabricated patterns, non-linguistic signals, literal translation, code switching, and time-gaining strategy. Meanwhile, there were eleven types of communication strategies which were used by the students, namely message abandonment, topic avoidance, circumlocution , approximation, word coinage, prefabricated patterns, non-linguistic signals, literal translation, code switching, appeal for help, and time-gaining strategy. The communication strategies that were most frequently used by the teacher and the students, i.e. code switching and time-gaining strategy. There were two main reasons of the teacher using communication strategies, namely in order to help the students to comprehend the lesson and to avoid misunderstanding or misconception. On the other hand the students’ reasons were because of language difficulty and anxiety in making mistakes. keyword : communication strategies, Dornyei’s theory, EFL